New finding of green algae with potential for algal biotechnology, Chlorococcum oleofaciens and its molecular investigation - Y. I. Maltsev; T. V. Konovalenko (Regulatory Mechanisms in Biosystems, 2017)
The practice of soil algology shows that algae from the order Chlamydomonadales are among the most poorly studied and difficult to identify due to the high heterogeneity of their morphology and ultrastructure. Only the involvement of molecular genetic methods usually makes it possible to determine their taxonomic status with high accuracy. At the same time, in the algae flora of Ukraine there are more than 250 species from the order Chlamydomonadales, the status of which in most cases is established exclusively on the basis of light microscopy. This work is devoted to the study of the biotechnologically promising green alga Chlorococcum oleofaciens, taking into account the modern understanding of its taxonomic status. Two new strains of this species, separated from samples of forest litter and oak forest soil (the Samara Forest, Dnipropetrovsk region), are described. The strains were studied at the morphological level by using light microscopy methods, as well as using molecular genetic methods based on the studies of the nucleotide genes sequences of the 18S ribosomal DNA (rDNA) and chloroplast rbcL genes, the topology of secondary structures of internal transcribed spacer 2 (ITS2). The obtained results helped to confirm the presence of C. oleofaciens in the algae flora of Ukraine. Also, the authors of the article discuss the differences in the secondary structure of ITS2 in different strains of C. oleofaciens associated with the presence of compensatory base change (CBC), hemi-CBC in helices I and II, as well as deletions in helix IV and providing a basis for the hypothesis of the existence of cryptic species within C. oleofaciens. The obtained data can be used at the stage of preliminary selection of biochemical research objects.